PS-B03-1: MECHANISM FOR INCREASED BLOOD PRESSURE VARIABILITY AND EFFECT OF AZELNIDIPINE IN RATS INFUSED WITH NORADRENALIN. (January 2023) - Jiang, Danfeng; Matsuzaki, Minami; Kawagoe, Yukiko; Kitamura, Kazuo; Tsuruda, Toshihiro; Kaikita, Koichi; Asada, Yujiro; Kato, Johji
Abstract : Objective: Augmented blood pressure variability (BPV) has been shown to be associated with cardiovascular diseases. There are various types of BPV depending on time periods for which BP levels are evaluated, while there are reportedly factors, such as aging and stiffened large arteries, which are related to any type of BPV. However, the mechanistic relationships between these factors and augmented variability remain to be specified. Recently, we found that 24-h BPV was augmented following continuous infusion of noradrenalin (NA) over 14 days in rats, assuming this animal as a model of augmented BPV of 24-h ambulatory BP monitoring (ABPM) of humans. The aim of the present study was to explore the mechanism underlying NA-induced BPV and the pharmacological action of the calcium channel blocker (CCB) azelnidipine, focusing on alterations in baroreceptor reflex sensitivity (BRS) and morphological findings of the aortic arch, where baroreceptors are thought to be located. Methods: Nine-week-old male Wistar rats were continuously infused with subcutaneous 30 ug/h NA with or without oral administration with 30 mg/kg/day azelnidipine for 14 days. BPV was evaluated by a coefficient of variation (CV) of BP recorded every 15 min under an unrestrained condition via an abdominal aortic catheter by a radiotelemetry system. To estimate BRS, data obtained from continuous BP monitoring were analyzed by a sequence technique with the software HemoLab. Sections of the aortic arch were stained with hematoxylin-eosin, and cross-sectional areas were determined by computerized measurement. Results: CVs of systolic and diastolic BP during 24-h period almost doubled at day 7 and 14 following continuous infusion of NA. Increased 24-h variabilities were accompanied by impaired BRS (P < 0.01) and thickened aortic media (P < 0.01) at day 14 of the infusion. Meanwhile, azelnidipine administration mostly (P < 0.01) suppressed NA-induced BPV, and significantly (P < 0.01) alleviated impairment of BRS and aortic medial thickening. When analyzed for all groups by a simple regression, CV of systolic BP at day 14 significantly correlated with reduction in BRS (r = 0.45, P < 0.01), which was associated with aortic medial area (r = 0.57, P < 0.01). Conclusions: The present findings suggest a possible mechanism underlying NA-induced BPV: aortic arch stiffened by medial thickening may be partly involved in impaired BRS, resulting in augmented BPV. Meanwhile, azelnidipine alleviated BPV, preserving BRS probably via inhibition of NA-induced aortic medial thickening in rats.